Editing Digests for Social Networks - Evgeniya Yu. Poselenova; Darya D. Shapolova (Виртуальная коммуникация и социальные сети)
Modern people want to keep the track of as many events as possible while saving as much time as possible and reducing the level of redundant information. Internet digests provide an opportunity to systematize online publications and structure relevant information while focusing on the main facts and ideas. The paper describes the algorithm, editing, and design of Internet digests in social media. The authors analyzed digest entries in the Russian VKontakte social network to identify the methods of collecting, processing, and structuring information at different stages of editing. The standard folding method proved to be especially efficient, considering the stylistic diversity of the source materials compiled. As a result, the editor has to standardize the style without violating the integrity of the original text, eliminating information noise, applying the principles of information literacy and multidimensionality, etc. These aspects determine the structure of the VKontate digest as title – lead – text – call to action – graphic elements. The authors developed procedures for digest editorial as a sequence of actions that provides a high-quality media product with a high coefficient of information efficiency. Editing improves the quality of the material while ensuring its relevance, reliability, and clarity, thus facilitating the reading comprehension.